Enhanced mechanical properties of additive manufactured Grade 91 steel. (1st July 2021) - El-Atwani, O.; Eftink, B.P.; Cady, C.M.; Coughlin, D.R.; Schneider, M.M.; Maloy, S.A.
Abstract: High temperature stability of the mechanical properties, including creep behavior, are important factors to consider in certifying additive manufactured (AM) steels for reactor operation. AM-Grade 91 steel, tested at RT is shown to possess high yield strength, strain hardening and ductility even after high temperature aging for extended hours. Enhanced creep resistance at 650 ⁰C is also evident in the AM Grade 91 steel compared to wrought Grade 91 steel tested at the same conditions. The diverse and complex microstructure of this AM steel allows for both enhanced strength and ductility but increases the ductile-to-brittle transition temperature in these steels. Graphical abstract: Mechanical properties of aged additive manufactured Grade 91 steel. Image, graphical abstract